The Ecofeminist Perspective on The Impact of Climate Change on Women's Health: Study Case of Coastal Women in Sendang Biru Hamlet, Indonesia - Rosalinda, Henny; Hadi, Rany; Andini, Amalia Nur (Jurnal Ilmiah Hubungan Internasional, 2024)
Climate change poses major challenges for vulnerable groups throughout the world, especially women in coastal areas of Indonesia. Climate change presents a complex set of challenges that disproportionately impact vulnerable groups, with women often bearing the brunt of the impacts due to existing socio-cultural norms and unequal access to resources and decision-making processes. In Indonesia, coastal communities face increasing risks from rising sea levels, extreme weather events and coastal erosion caused by climate change. Women, who are often the primary caregivers and resource managers in these communities, bear a disproportionate burden of disasters caused by climate change. They experience increased vulnerability due to socio-cultural norms, limited access to resources, and limited power in making decisions. The impacts of climate change on women in Sendang Biru coastal areas are seen in various forms, including increased economic insecurity, loss of livelihoods, increased health risks, and disrupted access to health facilities. In addition, women's traditional roles as natural resource managers and family caretakers make them vulnerable to environmental degradation and displacement. Integrating an ecofeminist perspective in climate change strategy and mitigation explains how coastal women are exposed to risk, experience vulnerability, face problems in access to health and safety. Keywords: Ecofeminism, Coastal women; climate change; health; global health